2018
DOI: 10.21815/jde.018.134
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits and Challenges of Collaborative Learning: Educating Dental and Dental Hygiene Students Together

Abstract: Most often, members of the dental team are educated in separate programs. These professionals then come together in practice to work as a team, often with limited knowledge about each other's roles. The aim of this study was to assess the perspectives of dental and dental hygiene students regarding collaborative learning after taking two courses together. Five years (2010–14) of survey data were collected from a convenience sample of dental and dental hygiene students. The dental hygiene students were in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…The second survey was an adaptation of the validated Modified Readiness for Interprofessional Learning Scale (RIPLS), which has been used to evaluate IntraPE and IPE in multiple studies. [6][7][8]12,21 An expert panel -comprising 6 professors and dentists in the UWSOD, the Associate Dean for Academic Affairs at the UWSOD, the EWU DH graduate faculty, and 1 EWU dentist -adapted the Modified RIPLS for this study. The end result was a 12-item questionnaire, using a 5-point Likert scale from Strongly Disagree (1) to Strongly Agree (5).…”
Section: Instrumentmentioning
confidence: 99%
See 4 more Smart Citations
“…The second survey was an adaptation of the validated Modified Readiness for Interprofessional Learning Scale (RIPLS), which has been used to evaluate IntraPE and IPE in multiple studies. [6][7][8]12,21 An expert panel -comprising 6 professors and dentists in the UWSOD, the Associate Dean for Academic Affairs at the UWSOD, the EWU DH graduate faculty, and 1 EWU dentist -adapted the Modified RIPLS for this study. The end result was a 12-item questionnaire, using a 5-point Likert scale from Strongly Disagree (1) to Strongly Agree (5).…”
Section: Instrumentmentioning
confidence: 99%
“…The same results were found in a 2018 study of the RIDE program, where DH and RIDE students surveyed immediately following their coursework generally thought IntraPE was beneficial to help them solve clinical problems and be better team members. 8 Jackson et al (2018) found RIDE students strongly agreed IntraPE would benefit dental students. 8 This is consistent with the findings of this study: most RIDE alumni agreed IntraPE benefited their learning.…”
Section: Teamworkmentioning
confidence: 99%
See 3 more Smart Citations